High-elasticity and high-flexibility structural adhesive and preparation method thereof
By using diamephenyl porphyrin and tetrasulfonic acid porphyrin in curtain wall structural glue to improve elasticity and adding nanoglass fibers to improve toughness and strength, the problem of insufficient elasticity and toughness of existing structural glues in extreme environments is solved, and a high elasticity and high flexibility structural glue suitable for a wide range of harsh environments is prepared.
Patent Information
- Application Number
- CN202411810222.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
When existing curtain wall structural adhesives cope with extreme environments, their elasticity and toughness cannot meet the needs, which poses safety risks.
High elasticity and high flexibility structural glue are prepared by using diaminophenyl porphyrin and tetrasulfonic acid porphyrin to improve the elasticity of the glue and improve the toughness and strength of the glue through nanoglass fibers.
The resulting structural glue is highly elastic and tough, can meet the needs of many harsh environments, has a wider range of application and reduces safety hazards.
Smart Images

Figure BDA0005180372990000071 
Figure BDA0005180372990000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of structural adhesives, in particular to a high-elasticity and high-flexibility structural adhesive and a preparation method thereof. Background Art
[0002] Curtain wall structural adhesive refers to an adhesive used in building curtain wall systems, especially in glass curtain walls and metal frame curtain walls, to play a structural connection and sealing role. It not only has strong bonding properties, but also can cope with changes in the external environment, including temperature fluctuations, wind pressure, vibration, etc.
[0003] Most of the existing curtain wall structural adhesives are single-component, greenhouse neutral curing silicone structural adhesives. When dealing with extreme environments, their elasticity and toughness cannot meet the requirements and there are safety hazards. Therefore, the present invention proposes a high-elasticity and high-flexibility structural adhesive and a preparation method. Summary of the invention
[0004] The object of the present invention is to provide a structural adhesive with high elasticity and high flexibility and a preparation method thereof, so as to solve the problems in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a structural adhesive with high elasticity and high flexibility. The components and contents of the structural adhesive are as follows, in parts by mass:
[0006] 45-65 parts of terminal hydroxyl polydimethylsiloxane, 1.4-3.6 parts of diaminophenylporphyrin, 0.7-1.8 parts of tetrasulfonate phenylporphyrin, 2-5 parts of composite titanium dioxide, 1.5-3 parts of nano glass fiber, 0.5-1 part of nano carbon fiber, 2-4 parts of nano silicon dioxide, 0.8-1.4 parts of curing agent, and 0.6-1.3 parts of anti-aging agent.
[0007] Preferably, the components and contents of the structural adhesive are as follows, in parts by mass:
[0008] 50-60 parts of terminal hydroxyl polydimethylsiloxane, 1.6-3 parts of diaminophenylporphyrin, 0.8-1.5 parts of tetrasulfonate phenylporphyrin, 2.6-4.3 parts of composite titanium dioxide, 1.8-2.4 parts of nano glass fiber, 0.6-0.8 parts of nano carbon fiber, 2.5-3.5 parts of nano silicon dioxide, 1-1.2 parts of curing agent, and 0.9-1.1 parts of anti-aging agent.
[0009] Preferably, the content ratio of diaminophenylporphyrin to tetrasulfonatephenylporphyrin is 2:1.
[0010] Preferably, the content ratio of the nano-glass fiber to the nano-carbon fiber is 3:1.
[0011] Preferably, the curing agent is one or more of diphenylmethanediamine, maleic anhydride, and diphenylmethanediisocyanate.
[0012] Preferably, the anti-aging agent is one or more of benzodithiazole, triphosphonate, and triglyceride.
[0013] The second aspect of the present invention provides a method for preparing the high-elasticity and high-flexibility structural adhesive according to the first aspect of the present invention, comprising the following steps:
[0014] S1, using tetraphenylporphyrin as raw material and concentrated sulfuric acid as sulfonating agent, reacting at 100-120°C for 4-6h, adding sodium hydroxide to adjust the pH value, filtering, washing with methanol, and obtaining tetrasulfonate phenylporphyrin;
[0015] S2, using tetraphenylporphyrin as raw material, fuming nitric acid as nitrating agent, and dichloromethane as solution, nitrating in an ice-water bath for 2-3 hours, and separating dinitrophenylporphyrin by column chromatography with dichloromethane and petroleum ether as eluents, and then reacting at 50-60°C for 4-6 hours with sodium sulfide as reducing agent and DMF as solvent, filtering, and separating diaminophenylporphyrin by column chromatography with dichloromethane and ethyl acetate as eluents;
[0016] S3, diaminophenylporphyrin and tetrasulfonate phenylporphyrin are mixed with other components in proportion, an appropriate amount of water is added, and the mixture is stirred at a high speed for 15 to 20 minutes to obtain a structural adhesive.
[0017] The present invention has at least the following beneficial effects:
[0018] The present invention provides a high-elasticity and high-flexibility structural adhesive and a preparation method thereof. The elasticity of the adhesive is improved by using diaminophenylporphyrin and tetrasulfonatephenylporphyrin, and the toughness and strength of the adhesive are improved by using nano-glass fibers. The prepared structural adhesive has high elasticity and toughness, can meet the use requirements of many harsh environments, and has a wider range of applications. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Example 1
[0021] A highly elastic and flexible structural adhesive, the components and contents of which are as follows, in parts by mass:
[0022] 45 parts of terminal hydroxyl polydimethylsiloxane, 1.4 parts of diaminophenylporphyrin, 0.7 parts of tetrasulfonate phenylporphyrin, 2 parts of composite titanium dioxide, 1.5 parts of nano glass fiber, 0.5 parts of nano carbon fiber, 2 parts of nano silicon dioxide, 0.8 parts of curing agent and 0.6 parts of anti-aging agent.
[0023] The content ratio of diaminophenylporphyrin to tetrasulfonatephenylporphyrin is 2:1; the content ratio of nano-glass fiber to nano-carbon fiber is 3:1.
[0024] Wherein, the curing agent is diphenylmethanediamine and the anti-aging agent is benzodithiazole.
[0025] The method for preparing the above structural adhesive with high elasticity and high flexibility comprises the following steps:
[0026] S1, using tetraphenylporphyrin as raw material and concentrated sulfuric acid as sulfonating agent, reacting at 100°C for 6 hours, adding sodium hydroxide to adjust the pH value, filtering, washing with methanol, and obtaining tetrasulfonate phenylporphyrin;
[0027] S2, using tetraphenylporphyrin as raw material, fuming nitric acid as nitrating agent, dichloromethane as solution, nitrating in an ice-water bath for 2 hours, the product is subjected to column chromatography with dichloromethane and petroleum ether as eluents to separate dinitrophenylporphyrin, then sodium sulfide as reducing agent, DMF as solvent, reacting at 50°C for 6 hours, filtering, and column chromatography with dichloromethane and ethyl acetate as eluents to separate diaminophenylporphyrin;
[0028] S3, diaminophenylporphyrin and tetrasulfonate phenylporphyrin are mixed with other components in proportion, an appropriate amount of water is added, and the mixture is stirred at a high speed for 15 to 20 minutes to obtain a structural adhesive.
[0029] Example 2
[0030] A highly elastic and flexible structural adhesive, the components and contents of which are as follows, in parts by mass:
[0031] 50 parts of terminal hydroxyl polydimethylsiloxane, 1.6 parts of diaminophenylporphyrin, 0.8 parts of tetrasulfonate phenylporphyrin, 2.6 parts of composite titanium dioxide, 1.8 parts of nano glass fiber, 0.6 parts of nano carbon fiber, 2.5 parts of nano silicon dioxide, 1 part of curing agent, and 0.9 part of anti-aging agent.
[0032] The content ratio of diaminophenylporphyrin to tetrasulfonatephenylporphyrin is 2:1; the content ratio of nano-glass fiber to nano-carbon fiber is 3:1.
[0033] Wherein, the curing agent is maleic anhydride and the anti-aging agent is triphosphonate.
[0034] The method for preparing the above structural adhesive with high elasticity and high flexibility comprises the following steps:
[0035] S1, using tetraphenylporphyrin as raw material and concentrated sulfuric acid as sulfonating agent, reacting at 110°C for 5h, adding sodium hydroxide to adjust the pH value, filtering, washing with methanol, and obtaining tetrasulfonate phenylporphyrin;
[0036] S2, using tetraphenylporphyrin as raw material, fuming nitric acid as nitrating agent, dichloromethane as solution, nitrating in an ice-water bath for 2.5 hours, the product is subjected to column chromatography with dichloromethane and petroleum ether as eluents to separate dinitrophenylporphyrin, then sodium sulfide as reducing agent, DMF as solvent, reacting at 55°C for 5 hours, filtering, and column chromatography with dichloromethane and ethyl acetate as eluents to separate diaminophenylporphyrin;
[0037] S3, diaminophenylporphyrin and tetrasulfonate phenylporphyrin are mixed with other components in proportion, an appropriate amount of water is added, and the mixture is stirred at a high speed for 18 minutes to obtain a structural adhesive.
[0038] Example 3
[0039] A highly elastic and flexible structural adhesive, the components and contents of which are as follows, in parts by mass:
[0040] 55 parts of terminal hydroxyl polydimethylsiloxane, 2.6 parts of diaminophenylporphyrin, 1.3 parts of tetrasulfonate phenylporphyrin, 3 parts of composite titanium dioxide, 2.1 parts of nano glass fiber, 0.7 parts of nano carbon fiber, 3 parts of nano silicon dioxide, 1.1 parts of curing agent and 1 part of anti-aging agent.
[0041] The content ratio of diaminophenylporphyrin to tetrasulfonatephenylporphyrin is 2:1; the content ratio of nano-glass fiber to nano-carbon fiber is 3:1.
[0042] Wherein, the curing agent is diphenylmethane diisocyanate and the anti-aging agent is triglyceride.
[0043] The method for preparing the above highly elastic and highly flexible structural adhesive comprises the following steps:
[0044] S1, using tetraphenylporphyrin as raw material and concentrated sulfuric acid as sulfonating agent, reacting at 120°C for 4 hours, adding sodium hydroxide to adjust the pH value, filtering, washing with methanol, and obtaining tetrasulfonate phenylporphyrin;
[0045] S2, using tetraphenylporphyrin as raw material, fuming nitric acid as nitrating agent, and dichloromethane as solution, nitrating in an ice-water bath for 3 hours, the product is subjected to column chromatography with dichloromethane and petroleum ether as eluents to separate dinitrophenylporphyrin, then sodium sulfide is used as a reducing agent and DMF is used as a solvent, reacting at 60°C for 4 hours, filtering, and column chromatography with dichloromethane and ethyl acetate as eluents to separate diaminophenylporphyrin;
[0046] S3, diaminophenylporphyrin and tetrasulfonate phenylporphyrin are mixed with other components in proportion, an appropriate amount of water is added, and the mixture is stirred at a high speed for 20 minutes to obtain a structural adhesive.
[0047] Example 4
[0048] A highly elastic and flexible structural adhesive, the components and contents of which are as follows, in parts by mass:
[0049] 60 parts of terminal hydroxyl polydimethylsiloxane, 3 parts of diaminophenylporphyrin, 1.5 parts of tetrasulfonate phenylporphyrin, 4.3 parts of composite titanium dioxide, 2.4 parts of nano glass fiber, 0.8 parts of nano carbon fiber, 3.5 parts of nano silicon dioxide, 1.2 parts of curing agent and 1.1 parts of anti-aging agent.
[0050] The content ratio of diaminophenylporphyrin to tetrasulfonatephenylporphyrin is 2:1; the content ratio of nano-glass fiber to nano-carbon fiber is 3:1.
[0051] Wherein, the curing agent is diphenylmethanediamine and the anti-aging agent is triphosphonate.
[0052] The method for preparing the above structural adhesive with high elasticity and high flexibility comprises the following steps:
[0053] S1, using tetraphenylporphyrin as raw material and concentrated sulfuric acid as sulfonating agent, reacting at 100°C for 4 hours, adding sodium hydroxide to adjust the pH value, filtering, washing with methanol, and obtaining tetrasulfonate phenylporphyrin;
[0054] S2, using tetraphenylporphyrin as raw material, fuming nitric acid as nitrating agent, and dichloromethane as solution, nitrating in an ice-water bath for 2 hours, the product is subjected to column chromatography with dichloromethane and petroleum ether as eluents to separate dinitrophenylporphyrin, then sodium sulfide is used as a reducing agent and DMF is used as a solvent, reacting at 60°C for 6 hours, filtering, and column chromatography with dichloromethane and ethyl acetate as eluents to separate diaminophenylporphyrin;
[0055] S3, diaminophenylporphyrin and tetrasulfonatephenylporphyrin are mixed with other components in proportion, an appropriate amount of water is added, and the mixture is stirred at a high speed for 15 minutes to obtain a structural adhesive.
[0056] Example 5
[0057] A highly elastic and flexible structural adhesive, the components and contents of which are as follows, in parts by mass:
[0058] 65 parts of terminal hydroxyl polydimethylsiloxane, 3.6 parts of diaminophenylporphyrin, 1.8 parts of tetrasulfonate phenylporphyrin, 5 parts of composite titanium dioxide, 3 parts of nano glass fiber, 1 part of nano carbon fiber, 4 parts of nano silicon dioxide, 1.4 parts of curing agent, and 1.3 parts of anti-aging agent.
[0059] The content ratio of diaminophenylporphyrin to tetrasulfonatephenylporphyrin is 2:1; the content ratio of nano-glass fiber to nano-carbon fiber is 3:1.
[0060] Wherein, the curing agent is maleic anhydride and the anti-aging agent is triglyceride.
[0061] The method for preparing the above structural adhesive with high elasticity and high flexibility comprises the following steps:
[0062] S1, using tetraphenylporphyrin as raw material and concentrated sulfuric acid as sulfonating agent, reacting at 120°C for 4 hours, adding sodium hydroxide to adjust the pH value, filtering, washing with methanol, and obtaining tetrasulfonate phenylporphyrin;
[0063] S2, using tetraphenylporphyrin as raw material, fuming nitric acid as nitrating agent, dichloromethane as solution, nitrating in an ice-water bath for 3 hours, the product is subjected to column chromatography with dichloromethane and petroleum ether as eluents to separate dinitrophenylporphyrin, then sodium sulfide as reducing agent, DMF as solvent, reacting at 50°C for 6 hours, filtering, and column chromatography with dichloromethane and ethyl acetate as eluents to separate diaminophenylporphyrin;
[0064] S3, diaminophenylporphyrin and tetrasulfonate phenylporphyrin are mixed with other components in proportion, an appropriate amount of water is added, and the mixture is stirred at a high speed for 20 minutes to obtain a structural adhesive.
[0065] In the present invention, the diaminophenylporphyrin and the tetrasulfonate phenylporphyrin are a conjugated ring composed of four pyrroles and having elasticity and a nearly planar surface, so the elasticity of the glue can be improved; the nano glass fiber can improve the toughness and strength of the glue.
[0066] A series of related tests were carried out on the products prepared in the above Examples 1-5, and the results are shown in Tables 1 and 2 below:
[0067] Table 1 Test items and test basis
[0068]
[0069] Table 2 Test results
[0070]
[0071] In summary, the structural adhesive prepared by the present invention has high elasticity and toughness and a wider range of applications.
[0072] The above shows and describes the basic principles, main features and advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.
[0073] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A highly elastic and flexible structural adhesive, characterized in that: The composition and content of the structural adhesive are as follows, in parts by mass: 45-65 parts of terminal hydroxyl polydimethylsiloxane, 1.4-3.6 parts of diaminophenylporphyrin, 0.7-1.8 parts of tetrasulfonate phenylporphyrin, 2-5 parts of composite titanium dioxide, 1.5-3 parts of nano glass fiber, 0.5-1 part of nano carbon fiber, 2-4 parts of nano silicon dioxide, 0.8-1.4 parts of curing agent, and 0.6-1.3 parts of anti-aging agent.
2. A highly elastic and highly flexible structural adhesive according to claim 1, characterized in that: The composition and content of the structural adhesive are as follows, in parts by mass: 50-60 parts of terminal hydroxyl polydimethylsiloxane, 1.6-3 parts of diaminophenylporphyrin, 0.8-1.5 parts of tetrasulfonate phenylporphyrin, 2.6-4.3 parts of composite titanium dioxide, 1.8-2.4 parts of nano glass fiber, 0.6-0.8 parts of nano carbon fiber, 2.5-3.5 parts of nano silicon dioxide, 1-1.2 parts of curing agent, and 0.9-1.1 parts of anti-aging agent.
3. A highly elastic and highly flexible structural adhesive according to claim 2, characterized in that: The content ratio of the diaminophenylporphyrin to the tetrasulfonate phenylporphyrin is 2:
1.
4. The high elasticity and high flexibility structural adhesive according to claim 1, characterized in that: The content ratio of the nano glass fiber to the nano carbon fiber is 3:
1.
5. The high-elasticity and high-flexibility structural adhesive according to claim 1, characterized in that: The curing agent is one or more of diphenylmethanediamine, maleic anhydride and diphenylmethanediisocyanate.
6. The high-elasticity and high-flexibility structural adhesive and preparation method according to claim 1, characterized in that: The anti-aging agent is one or more of benzodithiazole, triphosphonate and triglyceride.
7. The method for preparing a highly elastic and highly flexible structural adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, using tetraphenylporphyrin as raw material and concentrated sulfuric acid as sulfonating agent, reacting at 100-120°C for 4-6h, adding sodium hydroxide to adjust the pH value, filtering, washing with methanol, and obtaining tetrasulfonate phenylporphyrin; S2, using tetraphenylporphyrin as raw material, fuming nitric acid as nitrating agent, and dichloromethane as solution, nitrating in an ice-water bath for 2-3 hours, and separating dinitrophenylporphyrin by column chromatography with dichloromethane and petroleum ether as eluents, and then reacting at 50-60°C for 4-6 hours with sodium sulfide as reducing agent and DMF as solvent, and filtering, and separating diaminophenylporphyrin by column chromatography with dichloromethane and ethyl acetate as eluents; S3, diaminophenylporphyrin and tetrasulfonate phenylporphyrin are mixed with other components in proportion, an appropriate amount of water is added, and the mixture is stirred at a high speed for 15 to 20 minutes to obtain a structural adhesive.